Analysis of the Impact of the Covid-19 Pandemic on Family Harmony: Case Studies on Family with and without People with Special Needs - Qisti Aufa Afifah (Indonesian Journal of Community and Special Needs Education, 2021)
Purpose of this study was to know the impact of COVID-19 on family harmony. The research method used is a case study of 4 people who have families with different backgrounds, roles, and conditions (with and without people with special needs). Results showed that impact of COVID-19 to the family harmony caused decreases in domestic income, increases in frequency of family fights, financial management difficulties, and the double burden of the family, especially parents. These results come because there are actions that emerged after COVID-19 appeared, namely home quarantine and implementation of health protocols. This then necessitated adaptation in various sectors where working from home, school from home, and layoffs of employees. This research has an impact on analyzing family harmony during the COVID-19 pandemic for the development of sustainable family harmony to prepare families for unexpected future situations.